5′ Rapid Amplification of cDNA Ends and Illumina MiSeq Reveals B Cell Receptor Features in Healthy Adults, Adults With Chronic HIV-1 Infection, Cord Blood, and Humanized Mice - Waltari, Eric; Jia, Manxue; Jiang, Caroline S.; Lu, Hong; Huang, Jing; Fernandez, Cristina; Finzi, Andrés; Kaufmann, Daniel E.; Markowitz, Martin; Tsuji, Moriya; Wu, Xueling (Frontiers in Immunology, 2018)
Using 5’ RACE, Illumina MiSeq, and basic flow cytometry, we systematically analyzed the expressed B cell receptor (BCR) repertoire in 14 healthy adult PBMCs, 5 HIV-1+ adult PBMCs, 5 cord blood samples, and 3 HIS-CD4/B mice, examining the full-length variable region of μ, γ, α, κ and λ chains for V-gene usage, somatic hypermutation (SHM), and CDR3 length. Adding to the known repertoire, Illumina MiSeq consistently detected small fractions of reads with high mutation frequencies including hypermutated μ reads, and reads with long CDR3s. Additionally, the less studied IgA repertoire displayed similar characteristics to that of IgG. Compared to healthy adults, the five HIV-1 chronically infected adults displayed elevated mutation frequencies for all μ, γ, α, κ and λ chains examined and slightly longer CDR3 lengths for γ, α and λ. To evaluate the reconstituted human BCR sequences in a humanized mouse model, we analyzed cord blood and HIS-CD4/B mice, which all lacked the typical SHM seen in the adult reference. Furthermore, MiSeq revealed identical unmutated IgM sequences derived from separate cell aliquots, thus for the first time demonstrating rare clonal members of unmutated IgM B cells by sequencing.